PRELIMINARY STUDY ON BIOLOGICAL ASPECTS OF PAPUAN SEERFISH (Scomberomorus multiradiatus MUNRO, 1964) IN MERAUKE WATERS, PAPUA, INDONESIA - Duranta Diandria Kembaren; Adi Surahman; Tegoeh Noegroho (Indonesian Fisheries Research Journal, 2019)
Papuan seerfish (Scomberomorus multiradiatus; local: tenggiri papua) is an endemic species to the Papuan waters and distributed from the waters of Papua New Guinea to Merauke in Indonesia. The biological information of this species is little known. This study aimed to determine the biological aspects of Papuan seerfish to fill the research gap of this species. The data collection were conducted from February to November 2016. Biological parameters observation of the fish sample included of fork length (FL), sex, and maturity stages. All the data were analyzed using standard methods. The maximum length and weight of Papuan seerfish from Merauke waters were 49 cm and 908 g and this size became the largest published size ever. The sex ratio was in an equal condition and the growth pattern was isometric. Spawning occurs all year arounds and reach its peak on August. The relative condition factor of Papuan seerfish tend to be low in the reproductive periods. Papuan seerfish from Merauke waters were caught before reaching their size at maturity (Lc < Lm). For the sustainability of this resources and precautionary approach of fisheries management, it is suggested to apply the minimum catch size in 33 cm.